Impact of training on LinkedIn learning on the employees: an assessment on Square Pharmaceuticals limited - Nilormy, Mashiat Salsabil (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.